The Effectiveness Of Layanan Penguasaan Konten To Improve Students’ Learning Skills (The Comparison of Discussion and Giving Task Methods With Lecture and Interactive Methode) - Khutami, Syiddik (Konselor, 2015)
Learning skill was a system, method and technique of a knowledge acquired by the students and taught by the teacher briefly, effectively and efficiently. Layanan penguasaan konten was one of services in guidance and counseling activity which was indisputably effective to improve the students’ learning skill at school. This was a quasi experimental research which applied Pre-test Post-test Control Group Design. By using purposive sampling technique, the first year students of SMAN 1 Bonjol were chosen as the subject of the research. These students then were divided into experimental group and control group. Each group consisted of 30 students. The research findings indicated that in general, the layanan penguasaan konten was effective to improve the students’ learning skill. Specifically, (1) there was a difference between the learning skill of the students in the experimental group in pretest and posttest, (2) there was a difference between   the learning skill of the students in the control group in pretest and posttest, and (3) there was a difference between   the learning skill of the students in the control group and in the control group in posttest. Based on the research findings above, it was concluded that the students’ learning skill could be improved through layanan penguasan konten. This research had shown that to improve the students’ learning skill, it was important to conduct layanan penguasaan konten at school by the school counselor. For the upcoming researchers, it is possible to conduct similar researches with different contexts, and the results could be compared.